Analisis Human Error Terhadap Terjadinya Hilang Barang Pada Gudang Dengan Metode Sherpa And Heart di PT. XYZ - Rio Khairul Rizky; Asep Erik Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT. XYZ still often experiences differences in the goods in the warehouse due to several factors. This study was analyzed using qualitative and quantitative methods. The methods used in this research are the SHERPA method (Systematic Human Error Reduction and Prediction Approach) and the HEART method (Human Error Assessment and Reduction Technique). After analyzing in the last 3 months, it was found that human errors occurred in the checker, operation, and inventory sections. After performing calculations using the SHERPA and HEART methods, it is known that the most potential human error occurs in the checker section. Using the SHERPA method to predict human errors, it also analyzes tasks and identifies potential solutions for errors in a structured manner. The HEART method is a technique used in the field of human reliability assessment (HRA), for the purpose of evaluating the possibility of human errors that occur during the completion of certain tasks.